Processing‐induced degradation of nanoclay organic modifier in melt‐mixed PET/PE blends during twin screw extrusion at industrial scale: Effect on morphology and mechanical behavior. Issue 4 (30th September 2013) - Yousfi, Mohamed; Lepretre, Sophie; Soulestin, Jeremie; Vergnes, Bruno; Lacrampe, Marie‐France; Krawczak, P.
ABSTRACT Immiscible PET/PE blends (80/20 wt %) were prepared on an industrial twin‐screw extruder with and without different types of commercially available montmorillonites (Cloisite® C15A, C10A, and 30B), containing organic surfactants differing by their polarities and their thermal stability). XRD and TEM observations evidence an intercalated structure, C15A leading to a better dispersion compared to C30B and C10A. The size of the PE dispersed phase decreases upon addition of organoclays (OMMT), suggesting an efficient compatibilization. The most efficient compatibilizing effect is observed in the case of C15A (smallest droplet size and narrowest size distribution). Nevertheless, elongation at break in tension and impact strength of PET/PE blends drastically decrease upon addition of OMMT, whatever the organoclay added, due to a possible degradation of the clay surfactant during melt compounding, which counteracts the nanofiller compatibilization effect. Furthermore, similar PET/PE/OMMT blends prepared at a lab scale using a microcompounder are ductile contrary to those compounded in the industrial extruder, which show a brittle behavior. This difference was ascribed to the extrusion residence time (much higher in an industrial extruder than in a lab micro‐compounder), which appeared to be a key parameter in controlling the clay surfactant degradation and thus the end‐use properties of such immiscible blends. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39712.